CARACTERÍSTICAS GEOTÉCNICAS E HIDROGEOLÓGICAS DE SITIOS PROPUESTOS COMO RELLENOS SANITARIOS EN COSTA RICA - Mora, Rolando (2011)
In this paper the geological, soil mechanical, and hydrogeological conditions of six propousedlandfills were investigated and also the polution potencial of the groundwater was estimated with the Le Grandmethodology. The analysed sites are Paraiso, Oreamuno, Santo Domingo, Atenas, Puriscal, Bolivar y Cerro Botadero; the majority are placed in the Central Valley of Costa Rica, involving volcanic materials.The landfill Santo Domingo is receiving solid wastes since 10 years ago, this place is very close to the La Valencia well fields and La Libertad springs, which are used to supply potable water to the city of San Jose; the-refore the need for protection of the groundwater against polution is very important. As a first recommendation,various piezometers must be constructed near to the site, for the monitoring the groundwater quality.The residual soils of the Peña Negra Formation can be used for the impermeabilization of the Pozos landfill inPuriscal; the hydraulic conductivity of the materials of the upper part of the soilprofil vary from 5 x 10-4 to 5x10-6 cm/s, but the underlying materials are very fractured and their hydraulic conductivity can be higher; werecomend an adecuate soil seal at the base.In Atenas site, the wastes and leachate must be handled with care to prevent the contamination of thestreams. The Cerro Botadero site have a high polution potential, because the groundwater table is very clo-se to the surface, and the materials of the aquifer are gravel and sand, with moderate hydraulic conductivity.The monitoring of the water quality in the La Gata and Seca streams is recomended and an adecuate impermeabilization at the base.